Hubungan Kepuasan Kerja terhadap Kinerja Karyawan pada PT Glostar Indonesia 2 Departemen Gudang - Mochamad Afrizal Maulana; Agisna Tri Munandar (Institut Manajemen Wiyata Indonesia, 2019)
This research is motivated by the problem of turn over that continues to occur at PT Glostar Indonesia 2 Department of Warehouse. The results of interviews with managers and staff show the assumption that they generally think turn is normal. Then the purpose of this study was to determine the effect of job satisfaction on employee performance. The research method used is quantitative and associative methods. The sampling technique uses population sampling method, with 25 respondents. Data analysis used multiple regression analysis, t test, which was preceded by validity test, reliability test, normality test, heteroscedasticity test. The results of this study are job satisfaction has a significant positive effect on employee performance.